The ultimate goal and human nature in Thomas Aquinas an Francisco Su´arez - Yangali N´ú˜nez, Oscar Edmundo (2023)
The objective of this paper is to demonstrate that the conceptions that Thomas Aquinas and Francisco Su´arez have about happiness and human nature share a common structure, despite some differences around their conception of essence. None of the mentioned authors should be identified under the labels of intellectualism or voluntarism since they defend the essential unity of the cognitive and affective dimensions in the human being. First, I develop why Aquinas’s position has been labeled intellectualist and how to challenge this label. Second, I examine what position Su´arez shows and what are his nuances on the Thomist conception. Finally, I show what conciliatory point we find between both conceptions in order to obtain a better definition of the ultimate goal and of the authentic nature of the human being.